2018
DOI: 10.1002/bapi.201800006
|View full text |Cite
|
Sign up to set email alerts
|

Verhalten von aus Baustoffen ausgelaugten Bioziden bei der Bodenpassage

Abstract: Biozide werden zahlreichen Bauprodukten zum Schutz des Materials vor Bewuchs durch Algen, Pilzen und weitere Mikroorganismen zugesetzt (Filmkonservierung). Damit sie von den Zielorganismen aufgenommen werden können, müssen die Biozide eine gewisse Wasserlöslichkeit besitzen. Diese führt gleichzeitig dazu, dass die Wirkstoffe bei Regenereignissen aus den Bauprodukten ausgelaugt werden und mit dem ablaufenden Regenwasser in den Boden sowie in Grund‐ und Oberflächenwasser gelangen können. Von einigen Bioziden ist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…A number of transformation products were detected by LC-MS and LC-HRMS in photolysis experiments in which we exposed aqueous solutions of terbutryn, TBOH, TBOH-DesE, TB-DesE, TBSO, and terbumeton (each as a single substance in water) to UV radiation at either 254 nm or to a spectrum with its maximum at 350 nm for 48 h. In addition to the investigated substances, detected mass signals correspond to terbutryn transformation products that were previously reported: desbutyl-terbutryn [1], desthiomethylterbutryn [9], desthiomethyl-desethyl-terbutryn [9], desthiomethyl-desbutyl-terbutryn [9], desbutyl-2-hydroxy-terbutryn [9], 2,4-diamino-1,3,5-triazin [21], 2-hydroxy-4,6-diamino-1,3,5-triazin [22], and terbutryn-TP-210 [1]. Desethyl-terbumeton is mentioned as a transformation product of terbumeton [23].…”
Section: Terbutryn and Transformation Products In Paint Extractssupporting
confidence: 66%
See 1 more Smart Citation
“…A number of transformation products were detected by LC-MS and LC-HRMS in photolysis experiments in which we exposed aqueous solutions of terbutryn, TBOH, TBOH-DesE, TB-DesE, TBSO, and terbumeton (each as a single substance in water) to UV radiation at either 254 nm or to a spectrum with its maximum at 350 nm for 48 h. In addition to the investigated substances, detected mass signals correspond to terbutryn transformation products that were previously reported: desbutyl-terbutryn [1], desthiomethylterbutryn [9], desthiomethyl-desethyl-terbutryn [9], desthiomethyl-desbutyl-terbutryn [9], desbutyl-2-hydroxy-terbutryn [9], 2,4-diamino-1,3,5-triazin [21], 2-hydroxy-4,6-diamino-1,3,5-triazin [22], and terbutryn-TP-210 [1]. Desethyl-terbumeton is mentioned as a transformation product of terbumeton [23].…”
Section: Terbutryn and Transformation Products In Paint Extractssupporting
confidence: 66%
“…Studies of transformation products of diuron in runoff from construction products have considered mainly DCPMU and DCPU. So far, the occurrence of 3-(4-chloro-3-hydroxyphenyl)-1,1-dimethylurea, 3-(3-chloro-4-hydroxyphenyl)-1,1-dimethylurea in runoff [1] and in eluates from façade coatings [22] was also reported. Repeated analysis of the extracts from the white paint after long-term storage indicated that dichloroaniline and monuron were also formed during the experiments.…”
Section: Diuron and Transformation Products In Paint Extractsmentioning
confidence: 99%
“…It is slowly degraded by hydrolysis and biodegradation with a half-life of a month up to a year (Giacomazzi and Cochet, 2004). Johann et al (2018) showed an increase of sorption of diuron in the soil passage with an increase of organic matter. Bollmann et al (2017a) estimated a half-life of diuron of more than 2500 days in soil.…”
Section: Introductionmentioning
confidence: 99%